Gibah dan Fitnah dalam Pandangan Islam - Kusnadi Kusnadi; Khusnul Khatimah; Arham Hadi Saputra (LP2M IAI Muhammadiyah Sinjai, 2021)
The Qur'an is the main source of Islamic teachings and a way of life for every Muslim. The Qur'an not only contains instructions about the relationship between humans and their gods, but also regulates human relations with each other, as well as humans with the natural environment. To understand the teachings of Islam perfectly, it is necessary to understand the contents of the Qur'an and practice it in daily life seriously and consistently. In this case, we will discuss the arguments about slander and backbiting related to communication. Communication is conveying messages from one person to another as is the case with slander and backbiting, but these 2 things are more about telling, conveying information with something negative or wrong which is an act that is hated by Allah SWT. slander and backbiting are often limited to what is meant by slander and backbiting and have not led to the purpose of that meaning. Besides being descriptive, in its real meaning it is prescriptive (providing provisions and rules) and always aims for the good of mankind, so it is necessary to know and understand what is meant by slander and backbiting.